A Study of Shading Effect on Photovoltaic Modules with Proposed P&O Checking Algorithm - Rozana Alik; Awang Jusoh; Tole Sutikno (International Journal of Electrical and Computer Engineering (IJECE), 2017)
Sun irradiation levels and associated temperature changes are the main factors that influence the conversion of solar energy into electricity. Most energy is produced during a hot sunny day as the sun irradiation is at the maximum level and uniform throughout the solar photovoltaic (PV). However, most solar PV were frequently get shadowed, completely or partially, by the neighbouring buildings, trees and passing clouds. Consequently, the solar PV has lower voltage and current output; hence, multiple maximum power points (MPP) are existed on the PV curve, which could cause confusion to the conventional Maximum Power Point Tracker (MPPT) to track the true MPP for the PV system. Thus, it is important to examine the impacts of partial shading on the solar PV in order to extract the maximum possible power. This paper presents a MATLAB-based modelling for simulation and experimental setup to study the I-V and P-V characteristics of a solar module under a non-uniform irradiation due to partial shading condition (PSC).  Furthermore, this study is also proposed an effective method (a variable step size of P&O with checking algorithm) that is low cost and higher tracking efficiency. Thus, this study is essential in improving and evaluating any new MPPT algorithm under the PSC.